Effect of temocillin in combination with other beta-lactam antibiotics. - Verbist, L (1984)
The antibacterial interactions of temocillin with other beta-lactams were tested by checkerboard combination in Mueller-Hinton agar against 146 strains of members of the family Enterobacteriaceae, 35 Pseudomonas aeruginosa strains, and 35 Staphylococcus aureus strains. Most combinations showed a moderate degree of synergism. In only one Klebsiella strain was minor antagonism observed between temocillin and ampicillin.